Biophilic perceptions in the urban waterfront: analytical study of the Nile waterfront in Central Cairo. Issue 1 (1st January 2021) - Eid, Sarah; Khalifa, Marwa; Abd Elrahman, Ahmed S.
ABSTRACT: With most of the world`s population living in cities and urban areas, cities are currently seeking new strategies to integrate nature into the built environment. Urban waterways, and their adjacent urban areas, have been typically the main concern of these strategies. Urban waterfronts, although often sites of heavy development, are rarely designed to reflect the innate human need for contact with nature, commonly known as 'Biophilia'. Within this context, the main objective of this paper is to explore biophilic indicators in Central Cairo's waterfront, under the guidelines of 'Biophilic Urbanism' approach, which expands the practice of biophilia on the scale of cities and urban areas. The paper follows an analytical case study approach. Methods of data collection included a literature review, on-site observations, concurrent with semi-structured interviews when possible, and an online survey. An in-depth analysis of data was then carried out to assess the degree of integration of the Nile waterfront within the urban fabric of the city to identify biophilic perceptions in the waterfront. Results demonstrate that users of the Nile waterfront are rarely allowed physical access to the water. Visual access is mostly provided, with minor exceptions. Other cross-cutting findings indicate a lack of longitudinal and lateral social connectivity to the waterfront, lack of continuous appropriate pedestrian trails, and a general lack of green spaces and public amenities.